Education on Literacy of the Verses of the Qur'an:Mahmud Yunus Perspective on the Book of Tafsir Al-Qur'an Al Karim - Sarah Nur’aeni Khoiriyah; M. Slamet Yahya; Enjang Burhanudin Yusuf (Medina-te : Jurnal Studi Islam, 2026)
The Quran has placed great emphasis on educational literacy since the beginning of its revelation, thus establishing Muslims in history as a group that built a great civilisation and played a significant role as a centre of world knowledge. This is evidenced by the emergence of a strong intellectual tradition among Muslims, ranging from mastery of religious knowledge to the development of general knowledge. In this context, literacy is not merely the ability to read and write, but also encompasses the skills to understand, analyse, and critique various issues facing society. This article specifically discusses Quranic literacy education through the perspective of Prof. Mahmud Yunus, a legendary Indonesian exegete who wrote a monumental work entitled Tafsir Al-Qur'an Al Karim. This study employs a literature review approach with a content analysis method to explore the meaning of literacy in the verses of the Qur'an as confirmed by Mahmud Yunus. The results show that many verses of the Qur'an emphasise the importance of literacy, for example through the command to read (iqra'), write with a pen (qalam), and think critically about social reality and natural phenomena. Literacy in this perspective is seen as an important instrument for discovering new knowledge, developing traditional records, and building a culture of reflective thinking in society. Thus, literacy education based on the Qur'an can be the main foundation for Muslims in facing the challenges of the times while maintaining the relevance of Islamic teachings in modern life.